1999
DOI: 10.1161/01.str.30.11.2369
|View full text |Cite
|
Sign up to set email alerts
|

Forced Use of the Upper Extremity in Chronic Stroke Patients

Abstract: Background and Purpose-Of all stroke survivors, 30% to 66% are unable to use their affected arm in performing activities of daily living. Although forced use therapy appears to improve arm function in chronic stroke patients, there is no conclusive evidence. This study evaluates the effectiveness of forced use therapy. Methods-In an observer-blinded randomized clinical trial, 66 chronic stroke patients were allocated to either forced use therapy (immobilization of the unaffected arm combined with intensive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
192
4
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 644 publications
(211 citation statements)
references
References 23 publications
5
192
4
8
Order By: Relevance
“…12 Had the limits of agreement been greater than the MCID of 5.7, this would suggest that the ARA test would not be reliable enough to detect a difference that is considered to be clinically relevant. 18 The difference between groups that was found in the RCT exceeds the intrarater limits of agreement, which supports the validity of this finding as a "signal" surmounting the "noise" because of the variability of ratings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Had the limits of agreement been greater than the MCID of 5.7, this would suggest that the ARA test would not be reliable enough to detect a difference that is considered to be clinically relevant. 18 The difference between groups that was found in the RCT exceeds the intrarater limits of agreement, which supports the validity of this finding as a "signal" surmounting the "noise" because of the variability of ratings.…”
Section: Discussionmentioning
confidence: 99%
“…12 The randomized clinical trial included 66 subjects who met the following inclusion criteria: (1) a history of a single stroke, at least 1 year previously, resulting in hemiparesis on the dominant side; (2) a minimum of 20°of active extension in the wrist and 10°of finger extension; (3) ARA test score below 51 (max score, 57); (4) age between 18 and 80 years; (5) ability to walk indoors without a cane, indicating no major balance problems; (6) no severe aphasia (score ϾP50 on the Stichting Afasie Nederland test 15 ); and (7) no severe cognitive impairments (Mini-Mental State score Ն22). 16 The protocol was approved by the hospital's medical ethics committee, and all patients gave written informed consent.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…CIT has recently been shown to have advantages relative to neurodevelopmental treatment of equal intensity. 9 Other studies have reported that repetitive practice of hand and finger movements against loads resulted in greater improvements in motor performance and functional scales than Bobath-based treatment, 10 transcutaneous electric nerve stimulation, 10 and suprathreshold electric stimulation of hand and wrist muscles. 11 Parry et al 12 reported that additional treatment, in the form of repetitive practice of movements and functional activities with a trained assistant, was more effective than additional conventional treatment from a physical therapist that focused on teaching techniques and encouraging self-practice.…”
mentioning
confidence: 99%